"Three-dimensional evaluation of breast volume changes following autologous free flap breast reconstruction over six months". (April 2020) - Wilting, Floor N.H.; Hameeteman, Marijn; Tielemans, Hanneke J.P.; Ulrich, Dietmar J.O.; Hummelink, Stefan
Abstract: Objectives: To date, little is known about postoperative changes in breast volume after autologous breast reconstruction. The purpose of this retrospective study was to investigate breast volume changes following autologous free flap reconstruction and the factors affecting flap volume. Materials and methods: Patients who underwent deep inferior epigastric perforator, superficial inferior epigastric artery and profunda artery perforator flaps between December 2016 and January 2019 were included. Exclusion criteria were breast complications requiring surgical debridement, and the absence of at least two suitable three-dimensional images postoperatively. Three-dimensional stereophotogrammetry volume measurements were performed at the time of standard surgical check-ups. Changes in breast volume were modeled using a quartic polynomial curve function in a nested mixed effects model. Results: 136 breasts in 101 patients were included. An average decrease of predicted breast volume was found from 637.8 cc (95%-CI [624.4, 651.1]) at two weeks to 566.6 cc (95%-CI [535.1, 598.0]) after three and 567.6 cc (95%-CI [515.9, 617.6]) after six months postoperatively. Reconstruction timing and first postoperatively measured breast volume showed a statistically significant difference in initial reconstructed breast volume and in the shape of the relationship between time and breast volume, whereas autologous technique and BMI only showed a statistically significant difference in initial reconstructed volume and mastectomy indication in the shape of the relationship. Conclusion: The final overall flap volume decreased to 88.9% of its original volume after six months. Gaining more insight into the factors influencing flap volume is of crucial importance to facilitate predictable surgical outcomes.